UMMATAN WASAṬAN MENURUT M. QURAISH SHIHAB DALAM TAFSIR AL-MISBAH DAN RELEVANSINYA DENGAN NILAI-NILAI PANCASILA - Abdur Rauf (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
Quran idealizes Muslims as ummatan wasaṭan, but in reality Muslims are still far from the idealism of the Quran. This article discusses the ummatan wasaṭan according to Quraish Shihab in Tafsir al-Misbah. The aim is to find out the interpretations and concepts of ummatan wasaṭan according to Quraish Shihab, as well as the relevance of their interpretation to the values of Pancasila. This research is a library research. This research uses documentation techniques and descriptive-analytical methods. This research also uses the comparison method. The results of this study found that: according to Quraish Shihab, ummatan wasaṭan were moderate people, who were not inclined to the left and right so that led to a fair attitude, and the people who became witnesses and were witnessed by all parties so that he was made an example. The characteristics of ummatan wasaṭan according to Quraish Shihab are eight. (a) Faith in Allah and His Messenger; (b) Firmness; (c) Wisdom; (d) Unity and cohesion and brotherhood; (e) Justice; (f) Modeling; (g) Balance; and (h) Inclusive. M. Quraish Shihab’s interpretation of ummatan wasaṭan is relevant to the values of Pancasila as the basis of the Republic of Indonesia. Keywords: M. Quraish Shihab, Ummatan Wasaṭan, Moderate